Physiological demands of running at 2-hour marathon race pace - Jones, A. M.; Kirby, B. S.; Clark, I. E.; Rice, H. M.; Fulkerson, E.; Wylie, L. J.; Wilkerson, D. P.; Vanhatalo, A.; Wilkins, B. W. (Journal of Applied Physiology, 2021)
The requirements of running a 2-h marathon have been extensively debated but the actual physiological demands of running at ~21.1 km/h have never been reported. We therefore conducted laboratory-based physiological evaluations and measured running economy (O2 cost) while running outdoors at ~21.1 km/h, in world-class distance runners as part of Nike`s "Breaking 2" marathon project. On separate days, 16 world-class male distance runners (age, 29 ± 4 yr; height, 1.72 ± 0.04 m; mass, 58.9 ± 3.3 kg) completed an incremental treadmill test for the assessment of V.O2peak, O2 cost of submaximal running, lactate threshold and lactate turn-point, and a track test during which they ran continuously at 21.1 km/h. The laboratory-determined V.O2peak was 71.0 ± 5.7 mL/kg/min with lactate threshold and lactate turn-point occurring at 18.9 ± 0.4 and 20.2 ± 0.6 km/h, corresponding to 83 ± 5% and 92 ± 3% V.O2peak, respectively. Seven athletes were able to attain a steady-state V.O2 when running outdoors at 21.1 km/h. The mean O2 cost for these athletes was 191 ± 19 mL/kg/km such that running at 21.1 km/h required an absolute V.O2 of ~4.0 L/min and represented 94 ± 3% V.O2peak. We report novel data on the O2 cost of running outdoors at 21.1 km/h, which enables better modeling of possible marathon performances by elite athletes. Using the value for O2 cost measured in this study, a sub 2-h marathon would require a 59 kg runner to sustain a V.O2 of approximately 4.0 L/min or 67 mL/kg/min.